Společenství Cesty Síly: Jediismus v České republice - Horák, Pavel (Lidé města, 2013)
This article deals with Fellowship of the Way of Force, which is the only representative of Jediism in the Czech Republic. It was founded in 2012, and presently has 19 members. Their members consider Jediism as their "life belief". Jediism represented by Fellowship of the Way of Force is a typical example of contemporary postmodern religiousness, often referred to as spirituality. We understand spirituality in this theoretical framework in the manner that L. Woodhead and P. Heelas have defined it in their book The Spiritual Revolution (Oxford, Blackwell 2005). This theoretical introduction is followed by an analysis of two aspects of Jediism. One is the inspiration stemming from the Star Wars movies, and the second is the spirituality of Jediism. Also, we open the issue of mythology and its influence on the Jediism in general. The next part deals with the contemporary situation in the Czech Republic, describing the most important influences and movements present. Furthermore, we analyse the issue of whether the Jedis consider Jediism as a religion. They do not, however, consider it as such, since they reject its institutionalized form and strictly rooted doctrine. The negative opinion of the majority of Czech society towards religion in general is another factor. Jedis put emphasis on an individualistic approach. Jediism as such, as well as its followers, takes inspiration from various religions, traditions or techniques. One includes what they prefer in "their own Jediism". The conclusion of this treatise introduces the concept of the Force in Jediism and puts it in the wider context of contemporary spirituality in the Czech Republic.